Applicability of the Google Analytics tool to assist in strategic marketing decision-making: A case study in a company from Piauí (Research, Society and Development, 2024)
The use of Web Analytics tools has become crucial for understanding information about user behavior, evaluating website performance, optimizing marketing campaigns, and enhancing business decision-making based on data provided by these tools. However, the complexity of these tools and the lack of specialized technical knowledge often prevent companies from fully exploiting their technological potential. This study aims to explore the applicability of Web Analytics tools, particularly Google Analytics 4 (GA4), for strategic marketing decision-making. The WACIC methodology was applied, which structures data collection, information analysis, strategy definition, and application to achieve KPIs, indicators that assist in measuring the organization's objectives. Data was collected over a 45-day period from the website of a beauty company in Piauí. Through the available platform insights, a digital situation analysis and application of the WACIC method were carried out. The results show that using GA4 made it possible to collect detailed data on users, sessions, page views, and events, providing useful information for strategic adjustments. The analysis concluded that, despite technical and regulatory obstacles, the effective integration of Web Analytics tools can significantly increase the effectiveness of marketing campaigns and user experience, becoming a valuable resource for companies seeking to enhance their competitiveness in the digital market.